Predicting the Development of a Low Gas-Saturated Zone of the Medvezhye Field Based on Geological and Hydrodynamic Modeling - Artem A. Shirjaev; Kirill E. Vinogradov; Y. V. Vaganov; Vitaliya O. Naumenko (Qubahan Academic Journal)
Given the rising water cut and reduced gas flow rate at large fields in Western Siberia, the issue of further development of productive formations of such fields is urgent. The factor of efficient use of natural resources also needs to be considered for extraction to be the most productive. The study is devoted to the construction of a 3D geological model of the PK1 layer of the Medvezhye field and a 3D hydrodynamic model created on its basis. Four project variants for the development of the transition zone of the PK1 formation of the Medvezhye field are proposed. The forecast period spans from 2023 to 2060.